OPTIMASI DISTRIBUSI KONVEKSI PAKAIAN DENGAN PENDEKATAN SIMULASI (STUDI KASUS CV. XYZ) - Anisa Pauziah; Diki Muchtar; Muhamad Ihsan; Tarman (Journal of Management and Industrial Engineering (JMIE), 2024)
One of the biggest challenges faced by garment manufacturing companies is optimizing the distribution of products to improve operational efficiency and minimize costs. Timely and effective distribution is crucial to ensure customer satisfaction and maintain the company's competitiveness. Therefore, efforts need to be made to optimize the distribution system in garment manufacturing companies by utilizing the latest technology, one of which is through simulation approaches. The aim of this research is to apply simulation to optimize the clothing distribution at CV. XYZ and provide recommendations for improving efficiency and reducing distribution costs. To achieve the research objectives, a case related to the distribution system was selected and analyzed in depth, specifically at CV. XYZ. To analyze this case, this research employs a case study strategy focusing on data collection from relevant distribution systems. One of the tools used to describe the distribution process systematically is a flowchart, which provides a visual overview of the sequence and relationships between various stages in the distribution process. The simulation results indicate that the distribution system at CV. XYZ could be improved by increasing the schedule from once to twice, rather than by adding distribution units. In terms of costs, this approach reduces the expenses, with the additional schedule only adding a fuel cost of IDR 46,800,000, while adding units would incur a cost of IDR 615,600,000.